1994
DOI: 10.1152/jappl.1994.77.4.1602
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in ventricular stroke volume at apnea termination is independent of oxygen desaturation

Abstract: Patients with obstructive sleep apnea experience nocturnal hemodynamic oscillations in association with repetitive respiratory events. Apnea termination (recovery) is accompanied by the nadir of arterial O2 saturation (SaO2), changes in intrathoracic pressure, and arousal from sleep. To investigate separately the contributions of hypoxemia and of arousal from sleep to changes in cardiac function, we continuously measured left ventricular stroke volume (LVSV) and mean arterial pressure (MAP) in eight subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
3

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 0 publications
3
20
0
3
Order By: Relevance
“…As such, the restoration of blood gases (and removal of the chemoreflex stress) does not play a role in this regulation. Further, while the abrupt silencing of MSNA was simultaneous with inspiration, and the negative pressure generated by inspiration at end apnea could be expected to facilitate venous return, cardiac output is actually decreased transiently (13,14). In addition, previous research has demonstrated respiratory modulation of MSNA during both normal and positive pressure ventilation (23,33).…”
Section: Discussionmentioning
confidence: 99%
“…As such, the restoration of blood gases (and removal of the chemoreflex stress) does not play a role in this regulation. Further, while the abrupt silencing of MSNA was simultaneous with inspiration, and the negative pressure generated by inspiration at end apnea could be expected to facilitate venous return, cardiac output is actually decreased transiently (13,14). In addition, previous research has demonstrated respiratory modulation of MSNA during both normal and positive pressure ventilation (23,33).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, upper airway obstruction is associated with exaggerated negative intrathoracic pressure swings, increased systemic venous return and preload to the right ventricle along with increased left cardiac ventricle after load (23,24). Acute overload of the cardiac ventricles could promote release of brain natriuretic peptide from ventricular myocytes which induces vasodilation and natriuresis (25).…”
Section: Discussionmentioning
confidence: 99%
“…67,68 Our findings also do not support prior human studies suggesting that oxygen desaturation, rather than frequency of arousals from sleep, is associated with higher odds ratios for systemic hypertension. 69 Prior experiments have demonstrated that BP after apneic events rises even when hypoxemia is blunted through oxygen administration 70,71 and that CPAP, but not supplemental oxygen, can lower BP variability during sleep. 72 Together, these results suggest that repeated oxyhemoglobin desaturation may be a necessary component for the development of hypertension in patients with OSA, but that improving SpO 2 alone, without treating airway obstruction and arousal, may not be enough to reverse these effects on BP.…”
Section: Discussionmentioning
confidence: 99%